Errores de rogatorio en una inscripción del siglo XII (Estudios humanísticos. Geografía, historia y arte, 1995)
The present paper tries to insit on certain aspects of Professor Robert Favreau's study about The Inscriptions in the Chalice and the Patene of Abbot Pelagius in Louvre. We try to clarify the autorship of Abbot Pelagius who entrusts the making of these liturgic pieces and explain, under a Paleographic point of view. the textual mistakes of the patene inscription.